CHALLENGES AND ACTIONS REGARDING THE REHABILITATION OF DEGRADED LANDS: CASE STUDY FROM THE PACIFIC ISLAND OF GUAM - M.H. Golabi; C. Iyekar; M. J. Denney (Sociedade & Natureza)
Severely eroded lands of southern Guam are referred to as BadLands. These are actively eroding areas of very deep, well–drained saprolite derived from tuff and tuff breccia. These badlands are exposed to overland flow, wind and rain causing sever erosion as the result of rapid runoff from the pitted, sloping sites void of vegetation. Through soil removal or sediment transport, erosion also alters the inherent physical and chemical properties of these soils. This alteration resulted in degradation, in turn affecting the environment as well as water quality in the down stream. The on-site damage from erosion is indeed a problem to environmental ecosystem of the island. Sediment lost due to erosion clogs rivers, lakes, and waterways. It reduces the water storage capacity of reservoirs and canals and increases flooding.The challenge facing soil and environmental scientists is to develop conservation and restoration strategies at the farm as well as at the watershed level that address crop production and natural resources protection needs, within a framework of increasing environmental and financial constraints. In our soil conservation program at the College of Natural and Applied Sciences of the University of Guam we have adopted integrated approaches to evaluate a variety of strategies, including the effect of conservation tillage and residue management, crop rotation with leguminous plants (sunnhemp) as green manure as well as the use of composted organic wastes as soil amendment for organic matter build up, all for soil rehabilitation and restoration of the badlands in southern Guam. In a companion study we are evaluating the effectiveness of Vetiver technology as a sediment trap to mitigate sediment transport in a typical watershed basin in southern Guam. This paper discusses the methodology as well as up to date data that shows the effect of Vetiver technology on sediment trapping at the watershed level.